Utilization of Palm Plants (Arecaceae) in the Acehnese Community in Gandapura District, Bireuen Regency - Cut Roswita; Erlia Hanum; Afkar; Nadia Aldyza; Syifa Saputra; Rahmawati (Jurnal Penelitian Pendidikan IPA, 2026)
The purpose of this study was to determine the utilization of sugar palm (Arecaceae) plants in the Acehnese community in Gandapura District, Bireuen Regency. In collecting data, this study distributed questionnaires, semi-structured and open-ended free interviews to various age groups with a total of 11 questions. The research sample in this study amounted to 153 people. The sampling method was carried out using the purposeful sampling method; namely, the population has homogeneous and stratified elements/members. Samples were taken based on age groups, namely young adults (aged 20-35) who are actively working to earn a living; middle adults (aged 36-50) who are generally married and have a permanent residence; and older people (> 50 years) who are considered village leaders/elders and have influence in the village. The results showed that 13 types of sugar palm plants were utilized. The utilization of 13 types of plants consists of 7 types as food ingredients, 7 types as craft materials, 5 types as building materials, 7 types for traditional medicine, 2 types for traditional ceremonies and 5 types of ornamental plants. To determine the utilization of plant species diversity, an analysis of the level of importance of a plant species for the community was carried out, namely by calculating the Cultural Significance Index (ICS). The highest ICS value was found in the Cocos nucifera plant, namely 293, followed by Areca nut (Areca catechu) and Areca nut (Arenga pinnata) with values of 113 and 111.